REPAIR AND RESTORATION PROCESS OF THE TOPKAPI PALACE TABLAKAR WARD - Uysal Engudar, Ece; Yergun, Uzay (E.U. Printing and Publishing House, 2024)
The Topkap & imath; Palace, built in the second quarter of the fifteenth century in Sarayburnu, & Idot;stanbul, reflects the social, economic, administrative, military, artistic and cultural identity of the Ottoman Dynasty with its nearly five-century-old formation. After the foundation of the Topkap & imath; Palace consisting of administrative, residential, worship and service areas surrounded by fortification walls and gardens, its construction and repair process continued perpetually by virtue of its high population including sultan and his own family, palace women, internal and external servants until the nineteenth century. This process was related to the sultan's personal claim through the principle of practicality. Namely, if a palace structure was not useful anymore, it could be left idle and even demolished. In the nineteenth century, the palace was abandoned partially, hence, only visited in special occasions by the dynasty and shown around like a museum to foreign bureaucrats. This situation led the repair of the structures on visit route and service units solely, while the rest of them were left neglected and idle owing to the principle of practicality. After converted into a museum in 1924, the Topkap & imath; Palace lost its authenticity due to the prevalent tendency of stylistic unity under the name of supposed restorations especially in the Republican Era. Its late periodic Western layers were eliminated to transform the palace into the glorious days of the Ottoman Empire, the late ones were replaced with the classical ones, as well. Besides, using cement-based material on the invisible parts of a structure was not found inconvenient. The very late publication of the laws regarding the conservation and the inadequacies of them, limited perceptions of boards, poor documentation, mostly ignored boards' decisions, interpretation-based interventions, imprecise executions and priority of the museum function over the palace architecture enhanced this destruction. Of course, all of these circumstances had a serious impact on the Tablakar Ward, which is the subject of this study. Being an auxiliary branch of the palace kitchens, The Tablakar Ward, where tray carriers lived and kitchen utensils were kept, was tried to be sustained because it was an essential service unit in the Ottoman Era even in the nineteenth century. This permanence was ensured thanks to the various repair and consolidation methods such as maintenance, new planning or after disasters like earthquakes and fires. In Republican Era, through stylistic unity urge, its late periodic layers were eliminated and Ottoman classical architectural elements were added so as to revive an era. Moreover, by keeping its masonry structure shell the ward's interior was redesigned by using cement-based materials such as plaster, flooring, stairs, lintel and beam because of the fact that conserving the silhouette of a structure was the only matter during those days. Regardless of its authenticity, the ward was served as antique car section and police station and subsequently as fabric storage and archive. During this study, limited to the 15th century and 1962, the last essential restoration of the ward, conservation approaches across the country were examined within the framework of legal regulations, laws and institutional structuring, and these were compared with the Topkap & imath; Palace, palace kitchens and most recently the Tablakar Ward to acquire conservation process of the Tablakar Ward with the help of a literature review, board decisions and repair documents of The Ottoman Archives of the Turkish Republic Presidency State Archives.
Keywords: Conservation history; repair and restoration; Topkap & imath; Palace; palace kitchens ( Matbah-& imath; Amire); Tablakar Ward; Art